Drivers for a cross-sector successful collaboration: the Basque country model of action. Issue 2 (15th January 2020) - Enciso-Santocildes, Marta; Vidu, Ana; Gómez-Urquijo, Laura
Abstract : Purpose: The purpose of this paper is to show the positive effects of a cross-sector collaboration between public administration and third sector in the Basque Country. Solidarity within European society is a concern increasingly addressed from broader perspectives in broader territories. Civil society involvement has also reached public administrations. The European Commission H2020 project, SOLIDUS Solidarity in European societies: empowerment, social justice and citizenship (2016–2018), responds to the need to build a "renewed" Europe after the economic crisis, addressing social areas as employment, education, housing, health, civic engagement. Design/methodology/approach: The communicative methodology (CM) has been used in this research paper, including qualitative fieldwork involving representatives of third-sector organizations. The CM already showed its impact on society, through several research projects in which it has been applied. CM is based on including stakeholders' voices into research from the initial design until the end, responding their needs from research evidence. Thus, it contributes to put in common the knowledge of experts and stakeholders. Findings: Searching for successful practices of social innovation, this paper analyzed which elements enable such relationships between public administration and third-sector organizations to promote successful public policies. Even some risks and barriers have been highlighted, the authors' specific aim focuses on the positive aspects. Therefore, it shows drivers for a most efficient way of public management, which could potentially be extrapolated to other contexts. Some of these drivers are the following: support and collaboration between sectors, institutional trust, co-creation, active participation of the third sector, solidarity and commitment, efficient social policies and workers' professionalization. Originality/value: This paper contributes to returning to institutions and society the atmosphere of trust that the crisis context has damaged. The Basque Countries' comprehensive model of action proves to attend citizenship contributing to a better society, from engaging a successful collaboration across sectors. The creation of two models of collaboration helps to progress in the positive interaction between the third sector and government. This paper is also original because it gives voice to people directly involved on the field and uses their knowledge to describe drivers and assess collaboration and participation of the third sector. Peer review: The peer review history for this paper is available at: https://publons.com/publon/10.1108/IJSE-06-2019-0378